Corporate Social Responsibility: True Compromise or Simple Fashion? - Campuzano, Luis Felipe (2010)
This article explores the content and development of the concept of social responsibility. For this, it is based on the definition of the European Commission which states the following: "Corporate Social Responsibility is the voluntary integration by companies of a series of social and environmental concerns in their commercial operations and in relations with their interlocutors”. From this definition the analysis will seek to confront the current reality of CSR and raise some considerations to consider. Consequently, the emphasis is first on mentioning the aspect of voluntariness since it is the company itself that decides its participation. Second, mention is made of the personal decision of the company given that the author questions who is ultimately the one who must make the decision within the company. For this, the author thinks the need to give an internal focus of corporate social responsibility in the main interest group is the workers themselves. Third, it develops some social and environmental concerns that include the phenomenon of unemployment. Fourth, the author argues that CSR goes beyond the economic, given that the social interest is valued and, taken together, represents a sustainable balance. Finally, the author concludes by highlighting the following ideas: on the one hand, CSR is not social marketing and on the other hand, CSR is not social action with philanthropic objectives.